Insight into the Candidate Genes and Enriched Pathways Associated with Height, Length, Length to Height Ratio and Body-Weight of Korean Indigenous Breed, Jindo Dog Using Gene Set Enrichment-Based GWAS Analysis - Sunirmal Sheet; Jong-Seok Kim; Min-Jeong Ko; Na-Yeon Kim; Young-Jo Lim; Mi-Rim Park; Seung-Jin Lee; Jeong-Min Kim; Seok-Il Oh; Bong-Hwan Choi (Animals, 2021)
As a companion and hunting dog, height, length, length to height ratio (LHR) and body-weight are the vital economic traits for Jindo dog. Human selection and targeted breeding have produced an extraordinary diversity in these traits. Therefore, the identification of causative markers, genes and pathways that help us to understand the genetic basis of this variability is essential for their selection purposes. Here, we performed a genome-wide association study (GWAS) combined with enrichment analysis on 757 dogs using 118,879 SNPs. The genomic heritability (h2) was 0.33 for height and 0.28 for weight trait in Jindo. At p-value < 5 × 10−5, ten, six, thirteen and eleven SNPs on different chromosomes were significantly associated with height, length, LHR and body-weight traits, respectively. Based on our results, HHIP, LCORL and NCAPG for height, IGFI and FGFR3 for length, DLK1 and EFEMP1 for LHR and PTPN2, IGFI and RASAL2 for weight can be the potential candidate genes because of the significant SNPs located in their intronic or upstream regions. The gene-set enrichment analysis highlighted here nine and seven overlapping significant (p < 0.05) gene ontology (GO) terms and pathways among traits. Interestingly, the highlighted pathways were related to hormone synthesis, secretion and signalling were generally involved in the metabolism, growth and development process. Our data provide an insight into the significant genes and pathways if verified further, which will have a significant effect on the breeding of the Jindo dog’s population.